Identifikasi dan Distribusi Kutu Busuk (Cimex sp.) di Beberapa Pesantren Kota Palangka Raya - Elza Widya Putri; Astri Widiarty; Arif Rahman Jabal (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Bed bugs (Cimex sp.) are insects that can cause dermatitis, allergic reactions, and potential anemia through their bites, with their spread closely related to environmental hygiene and bedding conditions. This study aims to determine the presence and identify the types of bed bugs (Cimex sp.) found in Islamic boarding schools in Palangka Raya City. This quantitative descriptive study with a cross-sectional design was conducted in January 2024 at several boarding schools in Palangka Raya City to determine the presence and types of bed bugs (Cimex sp.) in students' bedrooms. The study samples included mattresses, pillows, blankets, carpets, and sofas in students' rooms with damp conditions and insufficient sunlight, using purposive sampling techniques. The equipment used included non-sterile gloves, flashlights, masks, head coverings, small bottles (100 cc urine pots), and label paper for visual inspection and sampling of Cimex sp. The results of the study in six Islamic boarding schools in Palangka Raya City showed the presence of bed bugs (Cimex sp.) on mattresses, pillows, dolls, and wooden cabinets, with macroscopic characteristics of black spots, particularly in the Nurul Solihin and Hidayatul Insan Islamic boarding schools, with a percentage of 33.3%. Nurul Solihin Islamic Boarding School had the highest number of Cimex sp., with 71 eggs, 32 nymphs, and 36 adult bed bugs. This finding indicates that the sleeping environment of students in some boarding schools has the potential to support the development of bed bugs. The study identified Cimex lectularis at the Nurul Solihin and Hidayatul Insan Islamic boarding schools, with life cycle stages found including eggs, nymphs, and adult bed bugs, and their habitats distributed across both boarding schools. These findings highlight the need for enhanced efforts to control bed bugs in boarding school environments. Keywords: Bed Bugs; Islamic Boarding Schools; Environmental Cleanliness